Ten years of specialized adult care for phenylketonuria: a single-centre experience - Mütze, Ulrike; Thiele, Alena Gerlinde; Bärwald, Christoph; Ceglarek, Uta; Kiess, Wieland; Beblo, Skadi (Orphanet journal of rare diseases, 2016)
Specialized adult care of phenylketonuria (PKU) patients is of increasing importance. Adult outpatient clinics for inherited errors of metabolism can help to achieve this task, but experience is limited. Ten years after establishment of a coordinated transition process and specialised adult care for inherited metabolic diseases, adult PKU care was evaluated with respect to metabolic control, therapy satisfaction, life satisfaction, sociodemographic data, economical welfare as well as pregnancy outcome.